Evaluation of Bio-Rad D-100 HbA1c analyzer against Tosoh G8 and Menarini HA-8180V - José María Maesa; Patricia Fernández-Riejos; Catalina Sánchez Mora; María de Toro; Paloma Menéndez Valladares; Concepción González-Rodriguez (Practical Laboratory Medicine, 2016)
Objectives: To evaluate the Bio-Rad D-100®, an HPLC analyzer for glycated hemoglobin (HbA1c) determination, and to compare its performance with the Menarini HA-8180V® and Sysmex G8®. Methods: Method comparison was performed according to Clinical and Laboratory Standards Institute (CLSI) EP9-A2 guidelines. We selected 100 samples from the routine laboratory workload and analyzed them in duplicate with the three analyzers. The imprecision study was performed according to CLSI EP5-A2 guidelines for both inter-assay and intra-assay variability. Bias was assessed with external quality control material. To establish linearity, CLSI EP6-A protocol was followed. Results: Method comparison (95% confidence intervals in parentheses): D-100 vs G8: Passing-Bablok regression; y=0.973(0.963–0.983)×−0.07(−0.07−0.069); r=0.9989. Bland-Altman mean difference: −0.229%HbA1c (−0.256: −0.202); Relative bias plot: D-100/G8 vs D100-G8 mean ratio=0.971(0.967−0.975). D-100 vs HA-8180V: Passing-Bablok regression; y=0.944(0.932–0.958)×−0.078(0.024−0.173); r=0.9989. Bland-Altman mean difference: −0.363%HbA1c (−0.401: −0.325); Relative bias plot D-100/HA-8180V vs D100-HA-8180V mean ratio=0.955(0.952−0.958). Inter-assay coefficient of variation (CV): 0.81%. Intra-assay CV: 1.04% (low level), and 0.78% (high level). Bias against target value=2.332%. Linearity: r2=0.998 in the concentration range 4.4−13.9%HbA1c. Carry-over: 0.0024%. Conclusions: The Bio-Rad D-100 shows good correlation with G8 and HA-8180V. There is a small proportional systematic difference (2.7% and 5.6%, respectively) in both comparisons. Inter and intra-assay CVs are both lower than the lowest CV obtained in studies performed with D-100 and other instruments. Keywords: Glycated hemoglobin, High performance liquid chromatography, Analyzer, Intra-assay variability, Inter-assay variability